-11-(-6-(3-5(8 divided by 4- 1))) simplify ​

Question

-11-(-6-(3-5(8 divided by 4- 1))) simplify ​

in progress 0
Liliana 3 weeks 2021-11-06T09:48:15+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-06T09:50:10+00:00

    Answer :

    = -11-(-6-(3-5(8 divided by 4- 1)))

    = -11-(-6-(3-5(8 ÷ 4- 1)))

    = -11-(-6-(3-5(2 – 1)))

    = -11-(-6-(3-5× 1))

    = -11-(-6-(3-5))

    = -11-(-6-(-2))

    = -11-(-6+2))

    = -11-(-4))

    = -11 + 5

    = – 6

    •°• The answer is 6 respectively !.

    _______________________

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )